2008
DOI: 10.1557/jmr.2008.0349
|View full text |Cite
|
Sign up to set email alerts
|

Size effects in LiF micron-scale single crystals of low dislocation density

Abstract: This study examines the size-dependent deformation response of pure LiF single crystals using microcompression testing. Microcrystals with an 〈001〉 orientation and sample diameter D ranging from 1 to 20 m were fabricated by focused ion beam (FIB)-milling from bulk crystals having a low initial dislocation density. Both as-grown and ␥-irradiated crystals were examined to characterize the effect of an increased point defect density on the size-affected plastic flow response. Similar to previously studied face-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
40
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 19 publications
3
40
2
Order By: Relevance
“…Our results contrast with previous studies that have shown strong size effects in the plastic deformation of fee metals (Uchic et al, 2004;Greer et al, 2005;Volkert and Lilleodden, 2006) and ionic compounds (Nadgorny et al, 2008;Dimiduk et al, 2010). In particular, Nadgorny et al (2008) reported a strong size effect in [100] oriented LiF micropiUars fabricated by FIB when the micropillar diameter was in the range 1-10 urn.…”
Section: Effect Of Micropillar Size and Ion Irradiationcontrasting
confidence: 99%
See 4 more Smart Citations
“…Our results contrast with previous studies that have shown strong size effects in the plastic deformation of fee metals (Uchic et al, 2004;Greer et al, 2005;Volkert and Lilleodden, 2006) and ionic compounds (Nadgorny et al, 2008;Dimiduk et al, 2010). In particular, Nadgorny et al (2008) reported a strong size effect in [100] oriented LiF micropiUars fabricated by FIB when the micropillar diameter was in the range 1-10 urn.…”
Section: Effect Of Micropillar Size and Ion Irradiationcontrasting
confidence: 99%
“…However, the fact that these micropiUars did not display a whisker-type behavior, controlled by the nucleation of dislocations (as the one observed in the Mo micropiUars of Bei et al (2008)), indicates the existence of an initial dislocation network caused by the thermal residual stresses developed upon cooling because of the differences in the coefficients of thermal expansion of both phases in the eutectic. So, both LiF micropiUars in Nadgorny et al (2008) and in this investigation contained a network of mobile dislocations prior to testing although the actual densities are unknown.…”
Section: Effect Of Micropillar Size and Ion Irradiationmentioning
confidence: 94%
See 3 more Smart Citations